Aluminum‐vacancy‐related dielectric relaxations in AlN ceramics. Issue 5 (18th December 2017) - Wang, Kang; Wang, Chunchang
Abstract: The dielectric properties of AlN ceramics were investigated comprehensively in the temperature range from room‐temperature to 950 K and frequency range of 10 2 to 5 × 10 6  Hz. The sample exhibits intrinsic dielectric behavior when T  < 500 K, showing a flat dielectric permittivity about 10 and an extremely low dielectric loss factor (tanδ < 2 × 10 −3 ). In the temperature above 500 K, two thermally activated dielectric relaxations related to bulk and interfacial effects were observed. Both relaxations strongly depend on the concentration of oxygen atoms. Our results indicate that the bulk relaxation, occurring in lower temperature range, is caused by aluminum vacancy hopping motion inside grains. The interfacial relaxation, occurring in higher temperature range, is caused by surface‐layer effect due to aluminum vacancies being blocked by sample‐electrode contact.